Optimalisasi Dan Simulasi Terhadap Perkembangan Kognitif Anak Usia Dini - Yusnita Yusnita (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2020)
Cognitive development is one of students’ development that emphases on knowledge –psychological process –to discover surroundings. Developing students’ knowledge is a teacher work. This is an analytical library research that is to show the optimization and simulation on development of the early childhoods’ cognitive. Piaget asserts four cognitive development which one of is preoperational stage. The stage is the early childhood development where they are in a golden age should be optimized through the education. At this stage, they learn through the use of symbols with the latest approach in learning. Teacher can help over the skills process and giving concepts for the students’ refinement of reasoning, so we should be aware of giving interpretation in class by giving them chances to express their ideas.